June 1941 : Hitler and Stalin - Lukacs, John, 1924-2019 (Yale University Press, 2006)
This new portrait of two great leaders confronting each other in June 1941 describes Hitler and Stalin's strange, calculating, and miscalculating relationship before the German invasion of Soviet Russia, with its gigantic (and unintended) consequences. Lukas questions many long-held beliefs. He suggests, for example, that among other things Hitler's first purpose involved England: if Stalin's Communist Russia were to be defeated, Hitler's Third Reich would be well-nigh invincible, and the British and American peoples would be forced to rethink the war against Hitler. Lukas presents evidence that Hitler (rather than his generals) had moments of dark foreboding before the invasion. Stalin could not, because he wished not, believe that Hitler would choose the risk of a two-front war by attacking him; he was stunned and shocked and came close to a breakdown. But he recovered, grew into a statesman, and eventually became a prime victor of the Second World War.--From publisher description.